Pakistan-US Relations: Impediments and the Way Forward - Muhammad Faisal (CISS Insight Journal, 2016)
In recent months policy differences between Pakistan and the United States (US) have complicated their already complex and tenuous bilateral relationship. Disagreements are being expressed in public, by both sides, over issues which form the broad contours of the relationship. Given the history of bilateral relationship over the past seven decades, it appears another break-down in ties is approaching. Officially the relations between the two states since October, 2001, have been labelled as a ‘strategic’, analysts in Islamabad and Washington, D.C., however, describe it as ‘transactional’. At present, US-Pakistan relationship is being viewed as a by-product of the US led war in Afghanistan. A war that has not gone well for Bush and Obama administrations over the last 15 years. Regional security environment in Pakistan’s neighborhood is also undergoing a change with active participation of the US. In this backdrop, stakeholders on both sides are faced with multiple issues, setting national priorities, and catering for divergent national interests.